2020
DOI: 10.1080/21691401.2020.1728287
|View full text |Cite
|
Sign up to set email alerts
|

KANK1 regulates paclitaxel resistance in lung adenocarcinoma A549 cells

Abstract: Paclitaxel (PTX), a tubulin-binding agent, is widely used and has shown good efficacy in the initial period of treatment for non-small cell lung cancer (NSCLC). However, the relatively rapid acquisition of resistance to PTX treatments that is observed in virtually all cases significantly limits its utility and remains a substantial challenge to the clinical management of NSCLC. The aim of this study was to identify candidate genes and mechanisms that might mediate acquired paclitaxel resistance. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Resistance to therapeutic drugs is a significant challenge affecting survival and prognosis for patients receiving medical treatment. Relevant studies have shown that, when a certain gene was abnormally methylated, the abnormal expression of that gene and resistance to anti-tumor drugs would develop (74)(75)(76)(77). Shen et al reported that decreased expression of the tumor suppressor gene KANK1 could increase paclitaxel resistance in non-small cell lung cancer (75).…”
Section: Drug Resistance Related To Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to therapeutic drugs is a significant challenge affecting survival and prognosis for patients receiving medical treatment. Relevant studies have shown that, when a certain gene was abnormally methylated, the abnormal expression of that gene and resistance to anti-tumor drugs would develop (74)(75)(76)(77). Shen et al reported that decreased expression of the tumor suppressor gene KANK1 could increase paclitaxel resistance in non-small cell lung cancer (75).…”
Section: Drug Resistance Related To Dna Methylationmentioning
confidence: 99%
“…Relevant studies have shown that, when a certain gene was abnormally methylated, the abnormal expression of that gene and resistance to anti-tumor drugs would develop (74)(75)(76)(77). Shen et al reported that decreased expression of the tumor suppressor gene KANK1 could increase paclitaxel resistance in non-small cell lung cancer (75). In CRC, NKX6.1 gene was demonstrated to participate in the regulation of chemotherapy sensitivity for its hypermethylation (78).…”
Section: Drug Resistance Related To Dna Methylationmentioning
confidence: 99%
“…Paclitaxel is a routine taxane-type chemotherapy drug for many cancers [5,6], including PCA [7]. Like in many other cancers [8,9], paclitaxel chemoresistance is a common problem existing in the process of PCA treatment [10]. That will result in the recurrence and metastasis of PCA, leading to poor survival of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…DOCK8 is involved in cytoskeleton remodeling, inducing migration in macrophages, Schwann precursors cells, T cells, and dendritic cells [31][32][33][34]. KANK1 participates in actin and microtubule regulation; however, its role in inhibiting or promoting migration depends on the system studied [35][36][37][38]. It has also been reported to play a role as a tumor suppressor gene [39,40].…”
Section: Introductionmentioning
confidence: 99%